RESPEITO AO BEM ESTAR DOS TRABALHADORES: MEDITAÇÃO PARA AMBIENTES ESTRESSANTES NA CONSTRUÇÃO - Dantas Filho, João Bosco P.; Barros Neto, José; Mourão, Carlos Alexandre M. Amaral; Rocha, Andréa Benício da; Luccas, Andre Vieira; Saggin, Angela de Bortoli (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Stressful environments are often found in construction industry which makes important to study the relation between stress and work. Alcohol or illicit drugs were reported to be common shortterm alternatives to reduce anxiety in male-dominated industries and have long-term implications for health and well-being. "What countermeasures can be used by construction workers?" A set of active coping strategies is identified, such as physical exercise, recreational activities and meditation. According to the Brazilian Ministry of Health, meditation is an instrument of physical, emotional, mental, social and cognitive strengthening that promotes concentration, stimulates well-being, relaxation, reduces stress, hyperactivity and depressive symptoms. "But would construction workers be willing to meditate?" The purpose of this paper is to assess the initial perceptions of construction workers under meditation training. This research has a qualitative approach and its strategy is a unique case study. Four meditation sessions were applied at the construction site during lunch break. Multiple sources of evidence were used: interviews and videos. The data analysis was qualitative. The results indicate: (1) construction workers consider that meditation values them and (2) they also recommend its implementation. This research gives some information that there is viability for meditation in construction.